Uptight responses between clenching and forearm raising with factors of visual feedback and maintenance effort in healthy young women: An experimental study on factorial design - Lijuan Zhou; Baoyong Li; Xianyu Zheng; Shaoxiong Guo; Yuan Zhang; Changsheng Chen; Kelun Wang; Meiqing Wang (BMC, 2023)
Abstract Background To achieve different central preset force levels requires various fine-tuning efforts and may elicit different uptight responses. The mandibular lever system has a distinct regularity in the fine-tuning function of the upper limbs. The purpose of the present study was to detect whether the uptight responses elicited from motivating clenching differ from those induced by motivating forearm raising at different force levels. Methods Twenty-five healthy females were enrolled in this study. The target was low, medium, and maximum force levels with or without visual feedback and/or maintenance effort. Surface electromyographic (SEMG) activity was recorded from the bilateral anterior temporalis and masseter or left biceps brachii muscle (BicL), and the T-Scan III System synchronously recorded the sensitive force values. The uptight responses and task difficulties were recorded for occlusal and left forearm lifting tasks using a unique visual analogue scale. Results The highest uptight response value was achieved at a low clenching force level with visual feedback requiring no maintenance effort but at a maximum forearm-raising force level with visual feedback and maintenance effort. The SEMG activities of both jaw-closing muscles and BicL were associated with the central preset force level (P < 0.001). However, the maintenance effort only increased the jaw-closing muscles' SEMG activity at the maximal force level (P < 0.001). Conclusions Clenching at the central preset lower force level with visual feedback is prone to elicit a higher degree of uptight response. The constant need for a low-intensity bite can have a negative effect on an individual's mood.